Developmental Plasticity in Response to Embryo Cryopreservation: The Importance of the Vitrification Device in Rabbits - Ximo Garcia-Dominguez; José Salvador Vicente; Francisco Marco-Jiménez (Animals, 2020)
In this study, we evaluated the effect of embryo vitrification using two different devices on adulthood phenotype in rabbits. In vitro development, prenatal embryo survival, body weight, growth performance, haematological and biochemical peripheral blood analysis, reproductive performance, and lactation performance traits were compared between the experimental groups. They derived from naturally-conceived embryos (NC), fresh-transferred embryos (FT), vitrified-transferred embryos using mini-straw (VTs), or vitrified-transferred embryos using Cryotop (VTc). Straw-vitrified embryos exhibited lower in vitro developmental rates and in vivo survival rates following embryo transfer compared to its Cryotop-vitrified counterparts. Moreover, the VTs group exhibited higher foetal losses than VTc, FT, and NC groups. Independently of the vitrification device, vitrified-transferred (VT) offspring showed a skewed sex ratio in favour of males, and an increased birth bodyweight. In contrast, postnatal daily growth was diminished in all ART (i.e., FT and VT) animals. In adulthood, significant differences in body weight between all groups was founded—all ART progenies weighed less than NC animals and, within ART, VT animals weighed less than FT. For VT groups, weight at adulthood was higher for the VTs group compared with the VTc group. Peripheral blood parameters ranged between common values. Moreover, no differences were found in the fertility rates between experimental groups. Furthermore, similar pregnancy rates, litter sizes, and the number of liveborns were observed, regardless of the experimental group. However, decreased milk yield occurred for VTc and FT animals compared to VTs and NC animals. A similar trend was observed for the milk composition of dry matter and fat. Concordantly, reduced body weight was found for suckling kits in the VTc and FT groups compared to VTs and NC animals. Our findings reveal that developmental changes after the embryo vitrification procedure could be associated with an exhibition of the embryonic developmental plasticity. Moreover, to our best knowledge, this study reports the first evidence demonstrating that the vitrification device used is not a trivial decision, providing valuable information about how the cooling–warming rates during vitrification can be partly responsible of the postnatal phenotypic variations.